An online interactive tool to assess visual environment in offices with roller shades. (September 2017) - Konstantzos, Iason; Tzempelikos, Athanasios
Abstract: The Visual Environment in perimeter office spaces is of interest in three different aspects: Visual Comfort, Lighting Energy Performance and Connection to the Outside, all of which are affected by a selection of design parameters, including the building's location, orientation, geometry and façade configuration (glazing and shading). This paper presents an interactive web-based tool for assessing the visual environment in office spaces with roller shades; it extends the three aforementioned metrics in an annual framework, and allows users to input the parameters of their space of interest and return design recommendations for visual comfort, lighting energy use and outside view based on fabric properties. The tool considers different locations, orientations, glazing properties and seating layouts and provides a straightforward and fast way to obtain preliminary information about the comfort, energy and view clarity performance of office designs will roller shades, without the need of high expertise or time-consuming simulations.